1990
DOI: 10.1295/koron.47.639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the molecular weights of raw epoxy resins on the physical properties of cured epoxy resins.

Abstract: Ltd. (4026, Kuji-cho, Hitachi-shi, 319-12 Japan) *2Hitachi Chemical Co ., Ltd. (1772-1, Kanakubo, Yuuki-shi, 307 Japan) The relationship between cross-linking density and physical properties was investigated for cured epoxy resins. These resins were prepared by using poly(glycidyl ether) of o-cresol-formaldehyde novolacs having different molecular weights, a phenol-formaldehyde novolac hardener, and various accelerators. The cross-linking density of the cured resins is higher for raw epoxy resins of higher mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies have been made on the relation between cross-linking density and physical properties for epoxy resins cured with various amine or acid anhydride hardeners, and it has been reported that similar relationships were observed for these epoxy resins.6-8J3- 27 We concluded in a previous paper [17][18][19][20] that the cross-linking density is the most dominant factor that determines the various physical properties of cured neat epoxy resins. The results show that there are relationships, given in Table V, between cross-linking density and physical properties of the cured resin; i.e., when the cross-linking density increases, the glass transition temperature also increases while the thermal expansion coefficient (TEC) in the rubbery region and elasticity in the glassy region decrease.…”
Section: As Shown Inmentioning
confidence: 85%
“…Many studies have been made on the relation between cross-linking density and physical properties for epoxy resins cured with various amine or acid anhydride hardeners, and it has been reported that similar relationships were observed for these epoxy resins.6-8J3- 27 We concluded in a previous paper [17][18][19][20] that the cross-linking density is the most dominant factor that determines the various physical properties of cured neat epoxy resins. The results show that there are relationships, given in Table V, between cross-linking density and physical properties of the cured resin; i.e., when the cross-linking density increases, the glass transition temperature also increases while the thermal expansion coefficient (TEC) in the rubbery region and elasticity in the glassy region decrease.…”
Section: As Shown Inmentioning
confidence: 85%
“…[5][6][7] Free volume measurement vs chemical conversion shows that the maximum in the isothermal density or modulus occurs approximately in the same location as the minimum found in the free volume. 8 The maximum found in density and modulus has a significant implication on all other physical properties, such as water absorption, 5 diffusion coefficient, 9 gas permeability, 9 thermal expansion coefficient, 10 and the physical aging rate. 11 Of most importance is that the same phenomenon has been observed in other systems, such as polycynurates 12,13 and phenolic resins.…”
mentioning
confidence: 99%